Aerobic Variables for Prediction of Alpine Skiing Performance – A Novel Approach - Nilsson, Robert; Lindberg, Ann-Sofie; Theos, Apostolos; Ferguson, Richard A.; Malm, Christer (Sports Medicine International Open, 2018)
The aim of this study was to investigate the predictive power of aerobic test results and anthropometric variables on FIS-ranking of junior elite alpine skiers. Results from twenty-three male and female adolescent elite alpine skiers from two seasons were included in the multivariate statistical models. Physical work capacity was determined by V̇O2peak, blood lactate concentration ([HLa]b), and heart rate (HR) during ergometer cycling. Anthropometric variables were body stature, body weight and calculated BMI. No significant correlation between competitive performance and aerobic work capacity or anthropometric data was observed neither in male nor female adolescent skiers. Pre-season physical tests and anthropometric data could therefore not predict end-season FIS-ranking. The best regression (R2) and prediction (Q2) models of FIS slalom (SL) and giant slalom (GS) rank reached R2=0.51 to 0.86, Q2=−0.73 to 0.18, indicating no valid models. This study could not establish V̇O2peak and other included variables as predictors of competitive performance. When combining results from commonly used tests for alpine skiers, and applying multivariate statistical models, investigated tests seems of limited used for athletes, coaches, and ski federations. Performance-specific pre-season tests must be developed and validated for prediction of performance and guidance of exercise training.
Keywords: exercise testing; athletic performance; FIS points; multivariate statistics; V̇O2max